Pemanfaatan Kulit Jagung dan Tongkol Jagung (Zea mays) sebagai Bahan Dasar Pembuatan Kertas Seni dengan Penambahan Natrium Hidroksida (NaOH) dan Pewarna Alami - Prasetyawati, Dwi Putri, Dra. Suparti M. Si (2015)
The cornhusk and corncob are part of plants that can be used as the base material of paper art. They have a high cellulose fiber content. The purpose of this study to determine the tensile strength, tear strength, and sensory test of art paper from cornhusk and corncob. This study used an experimental method with a completely randomized design (CRD) factorial design, with 3 repetitions. Factor 1 is the ratio of cornhusk with corncob (A), A1 (1: 1), A2 (1: 3), and A3 (3: 1). The second factor is the addition of teak leaves (B), B1: without teak leaves, B2: teak leaves 25g, B3: teak leaves 50g. The results showed art paper with the highest tensile strength and tear strength at treatment A3B3 (75g of cornhusk + 25g of corncob + 50g of teak leaves) 13.7116 N. Art paper with the lowest tensile strength at treatment A2B3 (25g of cornhusk + 75g of corncob + 50g of teak leaves) 6.9821 N. Art paper with the lowest tear strength at treatment A2B1 (25g of cornhusk + 75g of corncob without teak leaves) 7.6681 N. Art paper whose the most preferred is the treatment A3B1 (the color is yellow / bright, the fiber is not visible, and the texture is very smooth) and treatment A3B3 (the color is dark brown / assertive, the fiber is visible, and the texture is rough).